Personality : theory and research - Cervone, Daniel; Pervin, Lawrence A. (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2010)
"Now in its 11th edition, Personality: Theory and Research presents an unbiased introduction to the major theories of personality, successfully integrating theory with research in a scholarly, yet highly readable manner. Updated to include the latest research findings in the field, the new edition successfully captures the mystery of human personality and the efforts of psychologists to unravel it."--BOOK JACKET.
Ch. 1. Personality Theory: From Everyday Observations to Systematic Theories -- Ch. 2. The Scientific Study of People -- Ch. 3. A Psychodynamic Theory: Freud's Psychoanalytic Theory of Personality -- Ch. 4. Freud's Psychoanalytic Theory: Applications, Related Theoretical Conceptions, and Contemporary Research -- Ch. 5. A Phenomenological Theory: Carl Rogers's Person-Centered Theory of Personality -- Ch. 6. Rogers's Phenomenological Theory: Applications, Related Theoretical Conceptions, and Contemporary Research -- Ch. 7. Trait Theories of Personality: Allport, Eysenck, and Cattell -- Ch. 8. Trait Theory; The Five-Factor Model; Applications and Evaluation of Trait Approaches to Personality -- Ch. 9. Biological Foundations of Personality -- Ch. 10. Behaviorism and the Learning Approaches to Personality -- Ch. 11. A Cognitive Theory: George A. Kelly's Personal Construct Theory of Personality -- Ch. 12. Social-Cognitive Theory: Bandura and Mischel -- Ch. 13. Social-Cognitive Theory: Applications, Related Theoretical Conceptions, and Contemporary Research -- Ch. 14. Personality in Context: Interpersonal Relations, Culture, and Development Across the Course of Life -- Ch. 15. Assessing Personality Theory and Research.
Previous ed.: 2007.
Includes bibliographical references and index.
Keywords: Personality; Individuality